Effect of 1% chlorhexidine gel on the bonding strength to dentin - Mehmet Dalli; Ertuğrul Ercan; Yahya Orçun Zorba; Bayram İnce; Cafer Şahbaz; Emrullah Bahşi; Hakan Çolak (Elsevier, 2010)
The purpose of this in vitro study was to evaluate the effect of 1% chlorhexidine (CHX) gel on dentin bond strengths of posterior composite resin applied with two different adhesive systems. Material and methods: In total, 75 extracted, caries-free human molars were used. The occlusal surface of each tooth was ground to create a flat dentin surface. Then, each tooth was mounted in acrylic. The dentin specimens were randomly assigned to five groups of 15 specimens each. In Group 1, Prime & Bond NT (PBNT) was applied; in Group 2, a 1% CHX gel + etching for 15 s + PBNT were applied; in Group 3, etching + 1% CHX gel + PBNT were applied; in Group 4, Clearfil S3 Bond was applied; and in Group 5, 1% CHX gel + Clearfil S3 Bond were applied. A dentine bonding system was applied to dentin surfaces, and composite cylinders were built up using a special device and then light-polymerized. Specimens were mounted and sheared using an Instron universal testing machine at a cross-head speed of 0.5 mm/min. Results: The results were recorded in megapascals. The sheared specimens were examined under a light microscope, and the type of failure (adhesive, cohesive or mixed) was recorded. Data were compared by one-way analysis of variance and Tukey's honestly significant difference tests. Means were 16.4 ± 4.1 MPa in Group 1, 16.2 ± 3.9 MPa in Group 2, 13.0 ± 4.5 MPa in Group 3, 11.9 ± 2.7 MPa in Group 4, and 11.5 ± 2.7 MPa in Group 5. The use of 1% CHX gel before acid etching was significantly higher than after etching on the shear bond strength of PBNT (P < 0.05), but did not differ significantly from PBNT alone (P > 0.05). Conclusion: Within the limitations of the present in vitro study, it was concluded that 1% CHX gel application did not adversely affect the shear bond strengths of dentin-bonding agents.